2021
DOI: 10.1038/s41467-020-20602-5
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic neutralizing antibody targeting receptor binding domain of SARS-CoV-2 spike protein

Abstract: Vaccines and therapeutics are urgently needed for the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here, we screen human monoclonal antibodies (mAb) targeting the receptor binding domain (RBD) of the viral spike protein via antibody library constructed from peripheral blood mononuclear cells of a convalescent patient. The CT-P59 mAb potently neutralizes SARS-CoV-2 isolates including the D614G variant without antibody-dependent enhancement effect. Complex crystal structure of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
233
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(269 citation statements)
references
References 49 publications
11
233
0
2
Order By: Relevance
“…It was reported that SARS-CoV-2 preferentially replicates in the upper respiratory tract of ferrets, thus the relatively lower virus titer in the lower respiratory tract is likely in line with mild symptoms with SARS-CoV-2, which means it could represent of patients with asymptomatic to mild symptoms [ 22 , 23 ]. Such findings were consistent with the previous literature [ 16 ], thereby, the current study employed ferrets for the disease model, taking the intended indication of CT-P59 for treating patients with the mild symptoms into account. As expected, ferrets showed the lower virus titer in the lower airway than the upper airway, for the wild type virus.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It was reported that SARS-CoV-2 preferentially replicates in the upper respiratory tract of ferrets, thus the relatively lower virus titer in the lower respiratory tract is likely in line with mild symptoms with SARS-CoV-2, which means it could represent of patients with asymptomatic to mild symptoms [ 22 , 23 ]. Such findings were consistent with the previous literature [ 16 ], thereby, the current study employed ferrets for the disease model, taking the intended indication of CT-P59 for treating patients with the mild symptoms into account. As expected, ferrets showed the lower virus titer in the lower airway than the upper airway, for the wild type virus.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike LY-CoV555, CT-P59 was able to bind to RBD of B.1.351and neutralized B.1.351, albeit with reduced K D and IC 50 values. This is a suggestion that CT-P59 showed high barrier to resistant viruses since CT-P59 has relatively conserved residues for RBD binding although K417 and E484 are part of the epitope of CT-P59 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, early signals of efficacy from convalescent plasma therapy have encouraged isolation of multiple neutralizing SARS-CoV-2 mAbs 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 . Up to date, several single and combination mAb therapeutics have received emergency use authorization (EUA) 71 , 72 , 73 , including CT-P59 (granted in South Korea) 74 , LY-CoV555 alone or its cocktail with LY-CoV016 (granted in USA) 71 , 75 , 76 , and REGN-COV2 cocktail (granted in USA) 77 , 78 . Although the EUA of LY-CoV555 alone has been revoked by the US Food and Drug Administration (FDA) due to the sustained increase of resistant SARS-CoV-2 viral variants 79 , there are more candidates in the pipeline 80 .…”
Section: Antiviral Therapies Against Sars-cov-2 Cell Entrymentioning
confidence: 99%